Dari Pawai Obor ke Tilawah: Refleksi 1 Muharam Bersama KKN UNP Campago - Nurhasan Syah; Raffi Shabhan Rizqullah; Wilda Handayani; Vebby Sri Monika; Khaira Apriyana; Raisyah Fahma Nadira (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The commemoration of 1 Muharram organized by students of the Community Service Program (Kuliah Kerja Nyata/KKN) of Universitas Negeri Padang in Nagari Campago aimed to foster Islamic values and strengthen the religious character of the community, particularly among children. This activity was designed as an educational program integrated with local cultural traditions, including a torch parade and religious competitions such as Qur’anic Recitation (Musabaqah Tilawatil Qur’an/MTQ), Qur’an Memorization (Tahfidz), and the Adhan. All activities involved children from local Qur’anic learning centers (TPA) and received active participation from the community. This study employed a descriptive qualitative approach, with data collected through observation, documentation, and activity records during the implementation of the program. The results indicate an increase in religious enthusiasm, social participation, and stronger social cohesion among community members. Furthermore, the program contributed positively to children’s character development, particularly in enhancing self-confidence, fostering a love for the Qur’an, and encouraging the courage to perform in public. Support from community leaders and the local government played a crucial role in the successful implementation of this program